Enlightening Allostery: Designing Switchable Proteins by Photoreceptor Fusion - Mathony, Jan; Niopek, Dominik (Advanced biology, 2021)
Optogenetics harnesses natural photoreceptors to non-invasively control selected processes in cells with previously unmet spatiotemporal precision. Linking the activity of a protein of choice to the conformational state of a photosensor domain through allosteric coupling represents a powerful method for engineering light-responsive proteins. It enables the design of compact and highly potent single-component optogenetic systems with fast on- and off-switching kinetics. However, designing protein-photoreceptor chimeras, in which structural changes of the photoreceptor are effectively propagated to the fused effector protein, is a challenging engineering problem and often relies on trial and error. Here, recent advances in the design and application of optogenetic allosteric switches are reviewed. First, an overview of existing optogenetic tools based on inducible allostery is provided and their utility for cell biology applications is highlighted. Focusing on light-oxygen-voltage domains, a widely applied class of small blue light sensors, the available strategies for engineering light-dependent allostery are presented and their individual advantages and limitations are highlighted. Finally, high-throughput screening technologies based on comprehensive insertion libraries, which could accelerate the creation of stimulus-responsive receptor-protein chimeras for use in optogenetics and beyond, are discussed.